Dealing with the mess (we made): Unraveling hybridity, normativity, and complexity in journalism studies. (May 2019) - Witschge, Tamara; Anderson, CW; Domingo, David; Hermida, Alfred
In this article, we discuss the rise and use of the concept of hybridity in journalism studies. Hybridity afforded a meaningful intervention in a discipline that had the tendency to focus on a stabilized and homogeneous understanding of the field. Nonetheless, we now need to reconsider its deployment, as it only partially allows us to address and understand the developments in journalism. We argue that if scholarship is to move forward in a productive manner, we need, rather than denote everything that is complex as hybrid, to develop new approaches to our object of study. Ultimately, this is an open invitation to the field to adopt experientialist, practice-based approaches that help us overcome the ultimately limited binary dualities that have long governed our theoretical and empirical work in the field.